2005
DOI: 10.1111/j.1365-2141.2005.05550.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic criteria for monoclonal B‐cell lymphocytosis

Abstract: SummaryVery low levels of circulating monoclonal B‐cell subpopulations can now be detected in apparently healthy individuals using flow cytometry. We propose the term ‘monoclonal B‐cell lymphocytosis’ (MBL) to describe this finding. The aim of this document is to provide a working definition of MBL for future clinical, epidemiological and laboratory studies. We propose that the detection of a monoclonal B‐cell population by light chain restriction is sufficient to define this condition in individuals not meeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
308
0
18

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 365 publications
(328 citation statements)
references
References 37 publications
2
308
0
18
Order By: Relevance
“…Follicular lymphoma (FL) is one of the most common subtypes of NHL, with over 24,000 new cases diagnosed each year in the United States [1,2]. Prior to the rituximab era, FL had a median survival of 10 years, but progression varied and survival ranged from <1 year to >20 years after diagnosis [3].…”
Section: Author Contributionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Follicular lymphoma (FL) is one of the most common subtypes of NHL, with over 24,000 new cases diagnosed each year in the United States [1,2]. Prior to the rituximab era, FL had a median survival of 10 years, but progression varied and survival ranged from <1 year to >20 years after diagnosis [3].…”
Section: Author Contributionsmentioning
confidence: 99%
“…The Follicular Lymphoma International Prognostic Index (FLIPI) separates FL patients into three risk groups based on age, stage of disease, concentrations of b2-microglobulin and hemoglobin, nodal area involvement, serum lactate dehydrogenase levels, and bone marrow involvement [5,6]. Treatment strategies for FL have included ''watchful waiting,'' chemotherapy, immunochemotherapy, radiotherapy, radioimmunoconjugates, and stem cell transplantation [1]. Although new treatment strategies have changed the survival of patients with FL, patients continue to die from disease or complications of survival from disease [7].…”
Section: Author Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…blood, a B lymphocyte count <5.0 × 10 9 /L, and the absence of lymphadenopathy, organomegaly, or autoimmune/infectious disease as having MBL 4 . These criteria could cause confusion in patient classification as the diagnosis of CLL by the NCI 1996 criteria 1 is based on the ALC (an aggregate lymphocyte measure comprised of B cells, T cells, and NK cells) 1 whereas the diagnosis of MBL is based on the B lymphocyte count 4 .…”
mentioning
confidence: 99%
“…37 Approximately 1-2% of MBL patients per year progress to CLL, although many MBL patients never require therapy. 51,52 It should be noted, however, that this cutoff was chosen in a rather arbitrary fashion, and recent studies have attempted to define a biological cutoff threshold based on time to first therapy requirements. These studies have generally suggested that a higher cutoff, perhaps as high as 10-11 Â 10 9 , may be more useful for the distinction between MBL and CLL.…”
Section: Precursor Lesion-monoclonal B Lymphocytosismentioning
confidence: 99%